Exploring the Factors and Strategies in Implementation of Sustainable Land Transport System in Ayer Keroh, Melaka - Loo, H. S.; Chew, B. C.; Hamid, S. R. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
In Sustainable Development Goals (SDG), one of the goals is the development of sustainable cities and communities. In order to achieve this goal, sustainable transport system needs to be considered to enhance the development of the country. Ayer Keroh, Melaka is the most developed township in Malacca. This city consists of residential, industrial, commercial, tourist spots and administrative centers. Although it creates promising economy wealth, it also creates numerous socioenvironmental impacts due to the poor transport system. Most of the industries in the city prefer conventional transports for their logistics activities rather than green transports. The research was carried out through exploratory and qualitative method to get deeply insight in the green transport system field. Semi- structured interview was conducted by researcher with the policymaker team that formed by the staffs from municipal council and community representatives. The research was carried out to identify the factors that encourage the industry to utilize these green transport and strategies to help to reduce the usage of conventional transport. Two planning that based on foreign city experience were proposed to solve the problem of the usage for conventional transports.